IDENTIFIKASI KESULITAN BELAJAR SISWA PADA MATA PELAJARAN IPA KELAS V DI SD MUHAMMADIYAH SEMINGIN - Nurhikmah Nurhikmah; Ika Maryani (Jurnal Fundadikdas (Fundamental Pendidikan Dasar), 2018)
This study aimed to find out how to identify student learning difficulties in grade V science subjects at SD Muhammadiyah Semingin. This research is a type of qualitative research. The subject of research is the class teacher's and all of the V students of SD Muhammadiyah Semingin which amounted to 14 students, 10 male students and 4 female students. The object of research is identifying student learning difficulties. The data collection techniques in the form of observation, interviews and documentation. The data analysis tehnuque using descriptive quality analysis. The results showed that learning difficulties were caused by 1) the difficulty of difficult science material that often uses scientific language, 2) learning difficulties lack of concentration while studying, 3) learning difficulties arising from internal factors and external factors. Student internal factors include psycho-physical impairment or lack of students (cognitive, affective, and psychomotor). While the external factors of students include all the situations and conditions of the surrounding environment that do not support student learning activities. Learning difficulties must be taken in several stages of activities such as 1) Identifying students who are expected to experience learning difficulties; 2) Determine the factors causing learning difficulties; 3) Determine how to overcome them.